Association of sex hormones and glucose metabolism with the severity of multiple sclerosis. (1st September 2016) - Triantafyllou, Nikolaos; Thoda, Pinelopi; Armeni, Eleni; Rizos, Demetrios; Kaparos, George; Augoulea, Areti; Alexandrou, Andreas; Creatsa, Maria; Tsivgoulis, Georgios; Artemiades, Artemios; Panoulis, Constantinos; Lambrinoudaki, Irene
Abstract : Purpose/Aim of the study : We evaluated possible associations between the severity of multiple sclerosis (MS) and levels of sex hormones as well as biochemical parameters in a sample of ambulatory patients. Material and methods : This cross-sectional study recruited 133 adults (52 men, 66 premenopausal and 15 postmenopausal women), with relapsing-remitting MS. Fasting venous blood samples were drawn for biochemical and hormonal evaluation. These parameters were tested for possible associations with MS severity, assessed using the Expanded Disability Status Scale (EDSS)-scores. Results: Follicle-stimulating hormone correlated with mean EDSS scores ( r = −0.369, p = 0.038) in the premenopausal subgroup. However, this association became non-significant in the age-adjusted multivariate analysis ( p = 0.141; power = 67%, type α error 0.10). Free androgen exhibited a borderline negative effect on EDSS-scores in the subgroup of men ( r = −0.367, p = 0.093), which was lost after adjusting for age and duration of disease ( p = 0.192; statistical power = 93%, type α error 0.05). Levels of estradiol tended to affect disability status of postmenopausal women (normal–mild vs. severe impairment: 23.33 ± 11.73pg/mL vs. 14.74 ± 6.30pg/mL, p = 0.095). Levels of sex hormones or indices of glycemic metabolism did not differ between patients presenting with EDSS scores higher or lower than the median value. Conclusion : Sex hormones and indices of glucose metabolism exhibited only a middle effect on EDSS scoring, which was not independent from the presence of confounders like age and duration of MS. The present study highlights the need for additional research, in order to elucidate the role of sex hormones and insulin resistance in the course of MS.